Reasons that lead people to buy prescription medicines on the internet: a systematic review - Almomani, Hamzeh; Raza, Amna; Patel, Nilesh; Donyai, Parastou (Frontiers in Pharmacology, 2023)
Aim: This systematic review explores the factors that could influence consumer's decision of purchasing prescription medicines using the Internet.Methods: Relevant databases were searched to retrieve studies published from 2012 to 2021. The studies selected for inclusion were those focused on the consumer's perspective and the purchase of prescription medicines. A narrative synthesis was employed. The Capability Opportunity Motivation-Behaviour (COM-B) and the Theoretical Domains Framework (TDF) were employed as conceptual lenses that guided the analysis.Results: Seventeen studies were included. These studies have adopted various methodologies: qualitative method (n=4), quantitative method (n=12), and mixed methods (n=1). The studies were based in Europe (n=8), North America (n=3), Middle East (n= 4), and 2 studies were conducted in several countries (multinational). The analysis of these studies revealed 7 themes that represent the reasons that lead people to buy prescription medicines via the Internet. These themes were the consumers' beliefs about the outcomes of the purchase (perceived benefits and risks of the purchase), consumer's emotions that could influence the purchasing decision, the factors that increase or decrease consumer's level of behavioural control over the purchase (facilitators and barriers of the purchase), consumers knowledge about the purchase, the trusting beliefs that lead consumers to trust the online sellers of medicines, the social influencing factors, and the external environmental factors that could encourage the purchase.Discussion: This study provides a comprehensive review of the breadth of reasons that drive people to buy prescription medicines via the Internet. Identifying those reasons could provide the basis for regulators to design evidence-based awareness campaigns to minimise the purchase of prescription medicines via the Internet. Furthermore, future research directions have been provided in this review to build upon the existing knowledge and address the research gaps in this area.